The Influence of Main Reasons for Not Taking IFA Tablets on Adherence to ≥ 90 Tablet Consumption Among Pregnant Women - Kartikasari, Anggit; Cahyati, Widya Hary; Yuniastuti, Ari; Maharani, Chatila (Universitas Negeri Semarang, 2025)
Anemia during pregnancy is still a public health problem in Indonesia that affects mothers and babies. The government has implemented a supplementation program for iron tablets (IBT) to prevent anemia, but the compliance of pregnant women with these tablets is still low. Various factors, such as lack of awareness, side effects, and mothers’ perceptions of the importance of IBT, contribute to low compliance rates. This study analyzes the impact of the main reasons for not taking IBT on the number of tablets consumed during pregnancy based on data from the 2023 Indonesian Health Survey (SKI). This study used an analytical cross-sectional study design with secondary data from the 2023 Indonesian Health Survey. The independent variable was the main reason for not taking IBT, while the dependent variable was the number of tablets consumed during pregnancy (≥90). Data analysis was performed using correlation and regression. The results showed that the main reasons for not taking IBT were forgetting (30.39%), nausea/vomiting due to pregnancy (21.57%), bad taste and smell (12.60%), and side effects (12.57%). Most pregnant women did not reach the recommended consumption amount, with 60.37% consuming less than 90 tablets. The reason with the most significant influence on compliance was “not yet up to the end of time” (R=0.344, R²=0.117, p=0.030). The main factors influencing compliance of pregnant women in consuming iron tablets were perception of the need for supplements, side effects, and lack of awareness. Increasing education, social support, monitoring strategies, and reminders for consumption are needed to improve pregnant women’s compliance with iron tablets to reduce the incidence of anemia in Indonesia.